Second-best Congestion Pricing Schemes in the Monocentric City - Erik Verhoef (European Regional Science Association (ERSA), 2004)
This paper considers second-best congestion pricing in the monocentric city, with endogenous residential density and endogenous labour supply. A spatial general equilibrium model is developed that allows consideration of the three-way interactions between urban density, traffic congestion and labour supply. Congestion pricing schemes are analyzed that are second best `by design' (and not because distortions exist elsewhere in the spatial economy), like cordon charging and flat kilometre charges. Both for Cobb-Douglas utility and for CES utility, the analyses suggest that the relative welfare losses from second-best pricing, compared to first-best pricing, are surprisingly small.
Keywords: 330; JEL codes: R41; R48; D62